Women Migrants in Western Australia: Case Studies of Resilience and Empowerment. (March 2020) - Dantas, Jaya A. R.; Strauss, Penelope; Cameron, Roslyn; Rogers, Claire
This article presents findings from an exploratory research using descriptive case studies of 12 migrant women in Western Australia. The purposive sample represents the government, academia, the private sector, community, civil society and not-for-profit organisations and is ranged in age from the late 20s to the 70s. Underpinned by theoretical frameworks of resilience and empowerment, women have shared their personal case narratives, and five case studies are presented in this paper. Our findings resonate with the vital and uncontested importance of education, the desire to be empowered, the capacity to be resilient and adaptive and the importance of giving back to the community. Key recommendations include the need for migrant women's continued access to avenues of empowerment and furthering education. The provision of adaptive structures builds resilience and grows strong communities where women feel empowered. We propose that women migrants, through alliances and collaboration, cross borders of learning and work towards generating change and transformation.